STRATEGI PEMASARAN MELALUI KOMUNITAS GUNA MENINGKATKAN PENJUALAN IKAN PREDATOR: STUDI PADA TOKO IKAN HIAS GUBUK AQUATIC KERTOSONO - Hernanda, Sultanu Ahmaddiva; Bhirawa, Sigit Wisnu Setya; Kurniawan, Rony (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2025)
The purpose of this study is to describe the community-based marketing strategy implemented by Gubuk Aquatic Kertosono Ornamental Fish Store in marketing predator fish, as well as to identify the constraints and solutions in the implementation of the marketing strategy. This study employs a qualitative approach and is classified as a case study research design. The primary data were collected through in-depth interviews with three informants. The sampling technique used was snowball sampling, and informants were selected using the 5R criteria, namely relevance, recommendation, rapport, readiness, and reassurance. The data analysis in this study followed three stages: data reduction, data display, and conclusion drawing or verification. The findings indicate that the community-based marketing strategy implemented by Gubuk Aquatic Kertosono Ornamental Fish Store has proven effective in increasing predator fish sales. This strategy is realized through the formation of an active, communicative, and trust-based customer community. The community functions not only as a promotional medium but also as a platform for building long-term relationships between sellers and customers.It is recommended that the business consistently maintain and further develop the customer community, enhance the quality of communication, and preserve customer trust in order to sustain customer loyalty and increase sales performance. Future studies are expected to extend this research by adopting a quantitative approach or incorporating additional variables such as customer satisfaction and customer loyalty to strengthen the research findings.